2020
DOI: 10.48550/arxiv.2011.04667
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovering Strongly-lensed QSOs From Unresolved Light Curves

Yiping Shu,
Vasily Belokurov,
N. Wyn Evans

Abstract: We present a new method of discovering galaxy-scale, strongly-lensed QSO systems from unresolved light curves using the autocorrelation function. The method is tested on five rungs of simulated light curves from the Time Delay Challenge 1 that were designed to match the light-curve qualities from existing, ongoing, and forthcoming time-domain surveys such as the Medium Deep Survey of the Panoramic Survey Telescope And Rapid Response System 1, the Zwicky Transient Facility, and the Rubin Observatory Legacy Surv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 106 publications
(136 reference statements)
0
4
0
Order By: Relevance
“…A combination of these two approaches and crosschecks between their results offer the potential to deal with a broad range of transients. (While we focus on transients, combined lightcurves from quasars have been studied by, e.g., [23][24][25][26][27].) Future work will seek to improve further our approaches to classify various lensed transients and estimate their time delays.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of these two approaches and crosschecks between their results offer the potential to deal with a broad range of transients. (While we focus on transients, combined lightcurves from quasars have been studied by, e.g., [23][24][25][26][27].) Future work will seek to improve further our approaches to classify various lensed transients and estimate their time delays.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach is different than the one outlined by Geiger & Schneider (1996), Pindor (2005), and Shu et al (2020) in several respects. First, we use the fact that we have a statistical model for the light curve of quasars.…”
Section: Introductionmentioning
confidence: 89%
“…As discussed by Pindor (2005) and explained here, this is not always possible and requires a statistical model for the quasar variability. Recently, Shu et al (2020) demonstrated that a modified version of the auto-correlation function can recover the time delays of real systems with a success rate of about 20%.…”
Section: Introductionmentioning
confidence: 99%
“…For example, demonstrated that ignoring the correlations in quasar light curves results in significant underestimation of the time-delay uncertainties. Alternatively, Geiger & Schneider (1996), Pindor (2005) and Shu et al (2020) suggested using the auto-correlation (or related) function of the combined light curve of lensed quasars to measure their time delay. In Paper I (Springer & Ofek) we derive the likelihood function of the combined-flux of several time delayed light curves, given the free parameters (e.g., time delay, flux ratio).…”
Section: Introductionmentioning
confidence: 99%